Clinical characteristics and course of out‐of‐hospital shock in a national emergency medical services cohort. Issue 4 (23rd May 2020) - George, Timothy P.; Chan, Hei Kit; Crowe, Remle P.; Jarvis, Jeffrey L.; Jansen, Jan O.; Huebinger, Ryan M.; Wang, Henry E.
Abstract: Background: Shock from medical and traumatic conditions can result in organ injury and death. Limited data describe out‐of‐hospital treatment of shock. We sought to characterize adult out‐of‐hospital shock care in a national emergency medical services (EMS) cohort. Methods: This cross‐sectional study used 2018 data from ESO, Inc. (Austin, TX), a national EMS electronic health record system, containing data from 1289 EMS agencies in the United States. We included adult (age ≥18 years) non‐cardiac arrest patients with shock, defined as initial systolic blood pressure ≤80 mm Hg. We compared patient demographics, clinical characteristics, and response (defined as systolic blood pressure increase) between medical and traumatic shock patients, looking at systolic blood pressure trends over the first 90 minutes of care. Results: Among 6, 156, 895 adult 911 responses, shock was present in 62, 867 (1.02%; 95% confidence interval [CI] = 1.01%–1.03%); 54, 239 (86.3%) medical and 5978 (9.5%) traumatic, and 2650 unknown. Medical was more common than traumatic shock in women and older patients. The most common injuries associated with traumatic shock were falls (37.6%) and motor vehicle crashes (18.7%). Mean initial and final medical systolic blood pressure were 71 ± 10 mm Hg and 99 ± 24 mm Hg. Systolic blood pressure increased in 88.8% and decreased or did not change in 11.0%. Mean initial and final trauma systolic blood pressure were 71 ± 13 mm Hg and 105 ± 28 mm Hg; systolic blood pressure increased in 90.4% and decreased/did not change in 9.6%. On fractional polynomial modeling, systolic blood pressure changes were greater and faster for trauma than medical shock. Conclusions: In this national series, 1 of every 100 EMS encounters involved shock. These findings highlight the current course and care of shock in the out‐of‐hospital setting.